Influence Of Earnings Management, Profitability, And Liquidity On Stock Prices - Herman , Melyssa; Febriany, Novita (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2022)
This study aims to analyze the influence of earnings management, profitability, and liquidity of stock prices by focusing on food and beverage companies listed in Indonesia Stock Exchange with research period in 2016-2020. The data used in this research are secondary data. The population in this study are food and beverage companies listed in Indonesia Stock Exchange. The sampling selection method used was purposive sampling and obtained 11 companies. The analytical tool used in this study was the linear regression analysis. The results of this research showed that earnings management has a negative and significant effect on stock prices, profitability has a positive and significant effect on stock prices, and liquidity has a significant and negative effect on stock prices.